2018
DOI: 10.3390/molecules23010213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression Profiles of Sp-uchl3 and Sp-uchl5 during Gonad Development of Scylla paramamosain

Abstract: Ubiquitin C-terminal hydrolases (UCHLs) are a subset of deubiquitinating enzymes, and are involved in numerous physiological processes. However, the role of UCHLs during gonad development has not been studied in crustaceans. In this study, we have first cloned and analyzed expression profiling of Sp-uchl3 and Sp-uchl5 genes from mud crab Scylla paramamosain. The full-length cDNA of Sp-uchl3 is of 1804 bp. Its expression level in the ovary was significantly higher than in other tissues (p < 0.01), and during go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…UPP is involved in oocyte meiotic maturation as a key intracellular protein degradation system in the cell cycle ( Bebington et al, 2001 ). In crustaceans, Ubiquitin C-terminal hydrolases L3 ( UCHL3 ), UCHL5 , ubiquitin ribosomal protein S27 ( UbS27 ), ubiquitin ribosomal protein L40, and UPP system-related factors participate in the regulation of oogenesis ( Han et al, 2010 ; Wang et al, 2012 ; Han et al, 2018 ). In this study, we detected many genes in the pathway that changed in the ovary and hepatopancreas during ovarian development, such as UbS27a , ubiquitin-conjugating enzyme, ubiquitin carboxyl-terminal hydrolase isozyme L5, and ubiquitin-protein ligase.…”
Section: Discussionmentioning
confidence: 99%
“…UPP is involved in oocyte meiotic maturation as a key intracellular protein degradation system in the cell cycle ( Bebington et al, 2001 ). In crustaceans, Ubiquitin C-terminal hydrolases L3 ( UCHL3 ), UCHL5 , ubiquitin ribosomal protein S27 ( UbS27 ), ubiquitin ribosomal protein L40, and UPP system-related factors participate in the regulation of oogenesis ( Han et al, 2010 ; Wang et al, 2012 ; Han et al, 2018 ). In this study, we detected many genes in the pathway that changed in the ovary and hepatopancreas during ovarian development, such as UbS27a , ubiquitin-conjugating enzyme, ubiquitin carboxyl-terminal hydrolase isozyme L5, and ubiquitin-protein ligase.…”
Section: Discussionmentioning
confidence: 99%
“…UCHL3 is a subset of deubiquitinating enzymes, belonging to the ubiquitin c-terminal hydrolase family [ 19 ]. In recent years, the relationship between UCHL3 and DNA damage repair has received increased attention.…”
Section: Discussionmentioning
confidence: 99%
“…However, little information is available regarding the role of UCHLs in gonadal development of crustaceans. UCHLs have been identified only in S. paramamosain (Han et al, 2018). Han et al (2018) reported that the expression level of UCHL3 and UCHL5 in the ovary was significantly higher than in other tissues which provides basic data indicating that UCHL3 and UCHL5 may play important roles in the ovarian development of S. paramamosain.…”
Section: Ubiquitin C-terminal Hydrolases (Uchls)mentioning
confidence: 96%